Improvement of in vitro germination of Cycas revoluta zygotic embryos using gelrite as gelling agent - Benjelloun, Jalila; Taoufyq, Aida; El Abidine Triqui, Zine; Alami, Qamar Lahlimi; Layachi, Rajaa; Smouni, Abdelaziz; Bouzroud, Sarah; Guedira, Abdelkarim (Advances in Horticultural Science, 2020)
An efficient in vitro germination protocol for Cycas revoluta, a widespread ornamental tree, has been established using zygotic embryos as explants with a focus on mineral composition of the culture media, the gelling agent and cytokinine type. A high percentage of germination, 73% was obtained with SH medium instead of 27% with MS medium. A 100% of germination was obtained with the combination of SH medium and gelrite as gelling agent. The addition of cytokinines prompt shoot formation. An optimum shoot induction occurred using 0.5 mg/l of BAP where an average of 14.1 shoot were produced per explants while 2.2 shoots were formed in the presence of 2iP. A 100% of rooting was observed in the presence of 0.5 mg/l of 2iP whereas only 30% of shoots obtained on the SH medium with 0.5 mg/l of BAP were able to develop roots.